(untitled) (Communication & Society, 2019)
Since the argumentative turn in EU studies, research has shown that civil society activists can challenge frames promoted by EU institutions and incumbent groups, and influence public opinion in the EU. However, most studies of civil society mobilisation on EU issues have focused on the vertical framing of issues from Brussels to national capitals, rarely analysing mobilisation beyond Brussels. This article builds upon ongoing research on Spanish civil society activism on the TTIP (Bouza & Oleart, 2018) and framing EU issues on Twitter (Bouza & Tuñón, 2018), contributing to the study of the role of national activists in the horizontal translation of EU-wide mobilisation to national publics. We argue that national actors play an influential role in the discursive struggle to define ‘Europe’ and the EU in the (national) public spheres (Díez Medrano, 2003). Building on our previous analysis of national activism on TTIP in Spain, we analyse whether activists have engaged in a process of frame bridging (Snow et al., 1986), in order to expand the mobilisation against TTIP towards new issues and constituencies relating to the broader trade strategy of the EU. The present research addresses the role of the Spanish anti- TTIP social movement in the emergence, circulation and bridging of critical frames on the TTIP negotiations in the Spanish Twitter sphere. The article combines quantitative and qualitative methods –network analysis and framing analysis– in order to analyse the role of the @NoAlTTIP network in the building and diffusion of frames challenging the EU institutions discourse on trade in the Spanish context.